Kesihatan seksual dan reproduktif remaja menurut Islam - Abdul Hamid, Siti Hazariah; Hasan, Haliza; Md Isa, Muhammad Lokman; Uzir, Bisha Fathamah (2021)
KTP is a knowledge transfer program by the academician IIUM to the caretakers of a shelter home known as Darul Anisah. The training slides consist of topics (as stated above) that are a part of the Intellectual Property (IP) required to be produced under the allocation of the KTP-RIGS 19-025-0025 grant. This training slide is prepared based on the relevant topics for the Integrated sexual and reproductive health (ISRHeA) for adolescents Module. Four Training sessions have been conducted with caretakers and young women residing in Darul Anisah between November 2020 until December 2020 at Darul Anisah, Kg Chengal Lampung, Kuantan.